Pengaruh Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR) Debt to Equity Ratio (DER) Terhadap Return Saham Pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di BEI Pada Saat Pandemi Covid-19 (2020-2021) - Lainatusshifa Kemal (Jurnal Riset AKuntansi dan Bisnis, 2022)
The purpose of this study was to determine the effect of Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER) on stock returns in transportation and logistics companies listed on the IDX at the time of writing. Covid-19 pandemic (2020-2021 Period). This study used 15 companies. The approach used in this study is a quantitative approach, because the data measurement uses a numerical or numerical scale. The data used is secondary data. Analysis of the data used is multiple regression analysis. The results showed that Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER) had no simultaneous effect on stock returns. Partially Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER) also do not have a positive effect on stock returns in transportation and logistics sector companies listed on the IDX during the pandemic. . Covid-19 (2020-2021 Period)